Clinical presentation and molecular diagnosis of a possible Mpox virus and Varicella zoster virus co-infection in an adult immunocompetent Filipino: a case report - Balingit, April Keith; Grande, Phoebe Grace; Nicolasora, Amalea Dulcene; Polotan, Francisco Gerardo; Pantoni, Roslind Anne; Abulencia, Miguel Francisco; Chu, Maria Yna Joyce; Rivera, Nicole; Oblepias, Marie Socouer; Garcia, Jemelyn (Frontiers in Public Health, 2024)
We report the first travel-related case of a possible Mpox-Varicella zoster virus (VZV) co-infection in the Philippines, a country that is endemic for Varicella but non-endemic for Mpox. A 29-year-old Filipino, female, with a travel history to Switzerland and with no prior history of VZV infection sought consultation due to rashes. She presented with multiple papular, pustular, and vesicular skin lesions, some with umbilication and with irregular borders, on the face, neck, trunk, inguinal area, upper extremities, and right leg. She also had bilateral submandibular and post-auricular lymphadenopathies. Tzanck smear exhibited viral cytopathic effects. She tested positive for Mpox infection (Clade II) and Varicella infection via quantitative real-time polymerase chain reaction (qPCR) tests but with a high CT value obtained from the Mpox PCR. Shotgun metagenomic sequencing (mNGS) successfully recovered sequences from the Varicella zoster virus which corroborated with the high viral load detected using qPCR. In contrast, shotgun mNGS was not able to generate a Mpox consensus sequence due to very few reads mapped to the Mpox virus reference sequence, which raised the question if there was the presence of a true Mpox-Varicella co-infection in our patient. Nevertheless, systemic and topical acyclovir was given to the patient. She was discharged and continued home isolation for 30 days from the rash onset. Strategies have been formed by the country’s healthcare facilities to properly identify Mpox infection. However, Mpox co-infection with other viral diseases presented a challenge in the proper diagnosis of our patient. This prompted a high index of suspicion and the usage of suitable diagnostic tests. With proper clinical evaluation and utilization of appropriate diagnostic tests, we were able to diagnose the first Filipino patient with a possible Mpox and Varicella zoster virus co-infection.